Structure of Asclepias syriaca L. population against phytocenotic and habitat conditions in Widuchowa (West Pomerania) - Bacieczko, Wanda; Borcz, Agnieszka (Biodiversity: Research and Conservation, 2016)
Asclepias syriaca L. is on the invasive species list in Poland. Its sites are scattered, with the exception of cultivation sites; they are also not well identified in the country and that is why they have not been presented in the ATPOL (Distribution Atlas of Vascular Plants in Poland) yet. In this study, spatial structure of A. syriaca population against phytocenotic and soil conditions in Widuchowa (West Pomerania)were examined. Number of specimens, their density per 1 m2, and mean crowding were determined. In addition, the population spatial structure type was identified through observations and by calculation of the dispersion coefficient. On the basis of the conducted research, it was found that the investigated population comprised 1 500 specimens and occupied the area of 38 m2. It exhibited regular spatial distribution type (dispersion coefficient<1) and was characterized by high value of mean shoot density, which amounted to 29 spec./1 m2 (max. 35 spec./1 m2). On the basis of the conducted chemical analysis of the soil from the A. syriaca habitat, the substrate was classified as alkaline soil (pH=7.3-7.6), of low total nitrogen (0.07-0.15%), as well as low total carbon content (0.8-1.45%).